Tafsir Ayat Al-Qur’an Tentang Hijrah - Diena Qaulan Tsaqila; Aqbil Daffa Siahaan; Gusmita Zalianti; Jendri Jendri (Jurnal Budi Pekerti Agama Islam, 2025)
Hijrah is a monumental event in Islamic history, not only marking the Prophet Muhammad's move from Mecca to Medina, but also a symbol of profound spiritual and social transformation. The Quranic verses that narrate the hijrah, in addition to being a historical record, also contain universal meanings that are relevant to this day. This study aims to examine the meaning and relevance of the interpretation of Quranic verses about hijrah in the context of modern life. This research uses a descriptive qualitative approach to collect information from various sources. Hijrah refers to the departure of the Prophet Muhammad SAW from the city of Mecca to the city of Yastrib, which is now known as Medina. Hijrah started from the Prophet Muhammad SAW from Mecca to Medina. In Mecca, Muslims experienced systematic oppression by the polytheists, who ruled the region. Then Prophet Muhammad migrated to Medina due to increasing oppression in Makkah, which made the Muslims suffer. The Quranic verses on hijrah describe the process of change and struggle in building an independent and sovereign Muslim community. Interpretation of the verses on hijrah not only focuses on the historical aspects, but also emphasizes the meaning and values contained therein. A deep understanding of the interpretation of the verses about hijrah provides inspiration and motivation for Muslims to live a meaningful and meaningful life.